Primer on Demand-Side Management : With an Emphasis on Price-Responsive Programs - World Bank (Washington, DC, 2012)
The practice of Demand-Side Management (DSM) has evolved over the past three decades in response to lessons learned from implementation in different global settings, and also in response to the changing needs of restructured power markets. The most notable change that is occurring today is the inclusion of programs that emphasize price responsiveness in the DSM portfolio. Traditionally, DSM programs were confined to energy efficiency and conservation programs with reliability-driven load management programs being used occasionally to manage emergency situations. Electric prices were taken as a given when designing such programs, hampering the eventual success of all such efforts. This Primer has been written to introduce the new concepts of price-responsive DSM that are currently being investigated in a variety of different market settings. It highlights different criteria and taxonomies for classification and evaluation of DSM programs and recommends programs that will likely provide a better fit with the objectives, expected needs and outcomes of DSM initiatives in developing and transition countries. As defined in this primer, such initiatives include both load shifting programs (that either clip peak loads or shift energy used in the peak period to off-peak periods) and efficiency programs (that reduce the total amount of energy). The purpose of the primer is to provide successful examples of price-responsive DSM programs from the developed world and by discussing their workings, show that they can be also be applied to the developing world. Of course, before price-responsive programs can be implemented in the developing world, certain pre-requisites pertaining to metering and billing practices would have to be implemented. These are discussed in the report.